Räume und Grenzen in der Laienmetasprache. Eine Metaphernanalyse zu Sprache und Sprecher - Studler, Rebekka (Linguistik Online, 2017)
In folk linguistic studies people provide information about their perception and evaluation of languages and their speakers. In so doing, they use different strategies of verbalization. Frequently, they conceptualize space, boundaries, and crossings in drawing on mental concepts as metaphors and metonymies. This paper shows, based on a study on language attitudes in German-speaking Switzerland, the strategies laypeople use to organize their mental (language) spaces. For this purpose, I shall discuss recent data, collected via questionnaires and interviews, which illustrate how language attitudes are conceptualized and verbalized through metaphors and metonymies, and how the relationship between language and speaker is established through the process of indexicalization and iconization.